Audit Committee Size and IFRS Disclosure Compliance in the Tanzanian Banking Sector - Mwesigwa, Jordson Itekulana; Kapaya, Saganga; Layaa, John.N. (AGUSPATI Research Institute, 2025)
This study examines the effect of audit committee size (AUDCOMS) on the level of financial disclosure, measured using an IFRS disclosure index. A sample of 40 licensed banks was analyzed using robust regression to determine whether variations in audit committee size influence disclosure practices. The results show that audit committee size has no statistically significant effect on disclosure levels (β = −0.005, p = 0.609). This indicates that increasing the number of audit committee members does not necessarily improve the transparency or completeness of financial reporting. The findings suggest that factors other than committee size such as members’ audit expertise, independence, and effectiveness may play a more meaningful role in shaping the quality of financial disclosures. These insights underscore the need for governance reforms that prioritize competency and oversight quality over numerical composition.